The Molecular Mechanism of Transforming Growth Factor-β Signaling for Intestinal Fibrosis: A Mini-Review - Sun-Mi Yun; Seok-Ho Kim; Eun-Hee Kim (Frontiers Media S.A., 2019)
Inflammatory bowel disease is known as the most chronic inflammatory disorder in colon, which subsequently progresses to intestinal obstruction and fistula formation. Many studies to date for the treatment of IBD have been focused on inflammation. However, most of the anti-inflammatory agents do not have anti-fibrotic effects and could not relieve intestinal stricture in IBD patients. Because preventing or reversing intestinal fibrosis in IBD is a major therapeutic target, we analyzed the papers focusing on TGF-β signaling in intestinal fibrosis. TGF-β is a good candidate to treat the intestinal fibrosis in IBD which involves TGF-β signaling pathway, EMT, EndMT, ECM, and other regulators. Understanding the mechanism involved in TGF-β signaling will contribute to the treatment and diagnosis of intestinal fibrosis occurring in IBD as well as the understanding of the molecular mechanisms underlying the pathogenesis.